Academic Procrastination Analysis in Elementary School - Mawarni, Indah; Purnama, Ratih (Widyagogik, 2022)
The success of education in elementary schools will determine the success of education at the next level. But academic procrastination is one of the threats to the success of education in elementary schools. The objectives of this study were (1) to determine the academic procrastination of students in the class of SD Negeri 1 Nusa Raya, Belitang III sub-district. (2) To determine the factors that cause students' academic procrastination at SD Negeri 1 Nusaraya, Belitang III sub-district. This research uses descriptive qualitative research. The results showed that there was academic procrastination behavior at MTs Mambaul Ulum SD Negeri 1 Nusaraya, Belitang III sub-district, forms of academic procrastination behavior in students including delays and delays in collecting assignments, depending on friends, and poor time management. Factors that cause students to do academic procrastination Internal factors in the form of Lack of motivation to learn, self-discipline, and ideals to be achieved seriously, and also external factors, namely the environment, parenting patterns, and communication technology that affect participants’ students to procrastinate, be late and not submit assignments.